2018
DOI: 10.3892/etm.2018.6215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D on apoptosis of T-lymphocyte subsets in neonatal sepsis

Abstract: Effect of vitamin D on apoptosis of peripheral blood T-lymphocyte subsets in treatment of neonatal sepsis was investigated. A total of 150 neonatal patients with sepsis were randomly divided into vitamin D treatment group (observation group) and treatment control group, while 100 healthy newborns were selected as healthy control group. T-lymphocyte subsets were detected by flow cytometer, the levels of tumor necrosis factor-α, interleukin-1 and calcitonin were determined by double-antibody immunoluminometric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…[ 41 ] Vitamin D is a nutritional vitamin, but surveys have shown that children with critical illness have a high incidence of nutritional risk, and children with sepsis have a high incidence of nutritional risk of 86.4%. [ 40 ] In our meta-analysis, we demonstrated that critically ill children with sepsis might have a lower 25-OHD level than those without sepsis.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[ 41 ] Vitamin D is a nutritional vitamin, but surveys have shown that children with critical illness have a high incidence of nutritional risk, and children with sepsis have a high incidence of nutritional risk of 86.4%. [ 40 ] In our meta-analysis, we demonstrated that critically ill children with sepsis might have a lower 25-OHD level than those without sepsis.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, a total of 27 studies were included based on the inclusion and exclusion criteria. [ 3 , 7 10 , 19 40 ] The flowchart of the literature screening was shown in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also shown the impact of vitamin D deficiency on the regulation of immune responses by creating an antimicrobial peptide pattern in epithelial cells, neutrophils, and macrophages. There are also reports of lung non-maturation through examination of the nuclear vitamin D receptor (VDR) expressed in most body tissues, which contributes to cellular regulation, diagnosis, and differentiation in premature infants (15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…which can be due to maternal vitamin deficiency and causes serious problems in premature neonates, such as increased risk of respiratory problems at birth, osteopenia of prematurity, bronchopulmonary dysplasia, increased risk of infectious diseases, reduced brain growth, seizures, growth disturbances, retinopathy of immaturity, brain hemorrhage, and death (13)(14)(15). Studies report the effect of vitamin D deficiency on the regulation of immune responses by generating an antimicrobial peptide pattern in epithelial cells, neutrophils, and macrophages and the lack of lung maturation by examining the specific vitamin D receptor (VDR), which is expressed in most tissues of the body, in terms of regulation, diagnosis, and differentiation of the cell in immature died premature neonates (15)(16)(17)(18)(19)(20). Therefore, deficiency of this vitamin is one of the main challenges in the care of neonates (13).…”
Section: Introductionmentioning
confidence: 99%